Water and climate: Global environmental sustainability and the current state in a developing country, Nicaragua - Vammen, Katherine; Peña, Elizabet (Frontiers in Water, 2022)
Environmental sustainability means taking steps to secure adequate management of natural resources in all human productive activities. These steps involve a strategy of rational sustainable exploitation and the introduction of effective conservation measures. Unsustainable practices ranging from over-exploitation of resources to drastic land use changes have created environmental problems which consequently affect human well-being and health. Additionally, ecosystems and the quality of resources are under pressure which lead to a reduction in quality of water, forests and biodiversity. Climate change is exacerbating these problems and causing new ones. Globally, there exists scarcity of water and other resources such as energy which then lead to national or international social conflicts of use. Nicaragua, a prime example of a developing country with a vast richness in natural resources which brings potential to promote its own development, is on the same unsustainable path as the rest of the world with even greater challenges due to economic scarcity, high vulnerability to climate change and the lack of institutional capacity. After illustrating the present state of resources in Nicaragua, strategic suggestions of needed components for improving environmental management in this developing country have been laid out.